2021
DOI: 10.1101/2021.01.11.426045
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing scaling laws in gut microbial dynamics from time series data: caution is warranted

Abstract: Many studies have revealed that both host and environmental factors can impact the gut microbial compositions, implying that the gut microbiota is considerably dynamic1–5. In their Article, Ji et al.6 performed comprehensive analysis of multiple high-resolution time series data of human and mouse gut microbiota. They found that both human and mouse gut microbiota dynamics can be characterized by several robust scaling laws describing short- and long-term changes in gut microbiota abundances, distributions of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Since the distributions of , , and are dependent on correlations between sampling times, it was initially puzzling that their distributions in some data sets remained similar after shuffling sampling times, raising questions as to what extent these statistics hold information about the underlying intrinsic dynamics ( Tchourine et al, 2021 ; Wang and Liu, 2021a ). Our results assist in reconciling the apparent conundrum, since within our model richness and Taylor’s law exponent do not depend on correlations between sampling times and are also the statistics that are most informative about the intrinsic parameters and ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the distributions of , , and are dependent on correlations between sampling times, it was initially puzzling that their distributions in some data sets remained similar after shuffling sampling times, raising questions as to what extent these statistics hold information about the underlying intrinsic dynamics ( Tchourine et al, 2021 ; Wang and Liu, 2021a ). Our results assist in reconciling the apparent conundrum, since within our model richness and Taylor’s law exponent do not depend on correlations between sampling times and are also the statistics that are most informative about the intrinsic parameters and ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the nature of those scaling laws, we introduced a null model by randomly shu✏ing the time series to destroy the temporal structure in the original time series [29]. We found that most of the scaling laws can still be observed up to the change of the exponent values (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Second, what are the underlying mechanisms responsible for those scaling laws? Recently, we found that those scaling laws can still be observed from the shu✏ed time series of the human and mouse gut microbiomes, where the temporal structure in the original time series has been largely destroyed [29]. This finding prompts us to hypothesize that temporal fluctuations might be the key to explain those scaling laws.…”
mentioning
confidence: 93%
“…We are surprised by the letter by Wang and Liu 1 related to our recent study demonstrating that short- and long-term microbiota dynamics can be characterized by multiple macroecological relationships 2 . The discovery of these laws in microbiota represents an important advance in the understanding of microbial ecology.…”
Section: Figurementioning
confidence: 90%